Image encryption technique based on fractional chaotic time series. (May 2016) - Wu, Guo-Cheng; Baleanu, Dumitru; Lin, Zhen-Xiang
Chaos in discrete fractional maps has been reported very recently. In this study, the chaotic time series of fractional order is used in the scrambling technique and a novel image encryption scheme is designed. The fractional difference order and the chaotic coefficient play crucial roles in controlling chaotic behaviors. The encrypted results are analyzed, which shows that the encryption scheme is highly secure.